Sustainable Web Design - Greenwood, Tom (A Book Apart, 2021)
The internet may be digital, but it carries a very physical cost. From image files to colors to coding languages to servers, the choices we make in our web work can eat up electricity and spit out carbon-and as the internet grows, so does the cost to the environment. But there's hope: small, thoughtful changes in design and development can reduce the damage, while also making the web more resilient in the face of a changing climate. In Sustainable Web Design, Tom Greenwood offers a practical path to faster, more carbon-efficient websites that are not only better for the planet, but better for our users.